Constrained Application Protocol of Internet of Things - Thirupathi, V.; Saritha, Banala; Chitti, Sridevi (International Journal of Engineering and Technology, 2018)
Constrained Application Protocol (CoAP) is an application layer protocol of Internet of Things (IoT) protocol stack. It allows tiny devices to communicate with other tiny devices or constrained devices which uses similar protocols. CoAP is mainly developed for devices like low power and constrained lossy networks. These tiny devices may built using 8 bit microcontrollers with limited Random Access Memory (RAM) , Read only memory (ROM) and constrained networks like 6LoWPANs (IPV6 low power wireless personal area networks). This paper explains constrained application protocol and its applications.Â Â Â